Residual Life Calculation of Fatigue Crack Growth of Spinning Pulley - Weng Jiancheng; Shi Wenjie (Jixie chuandong, 2017)
The initial crack along the circumferential extension model of spinning pulley is established by using workbench based on the theory of linear elastic fracture mechanics,and the stress intensity factors of the crack front are calculated. The conclusion is drawn that the type of cracked in spinning pulleys is opening crack. Then,the different crack growth models of spinning pulley are established,the stress intensity factors of crack front and the amplitude ΔK of stress intensity factor are calculated. According to Paris formula and the curve of ΔK-a,the residual life of fatigue crack growth in the spinning pulley is calculated. The method provides a new way of calculating residual life of fatigue crack growth,with positive reference value for the safety design in the spinning pulley.